A Critical Realist Proposal on Planetary Oneness Paradigm - Shakespeare, Rodney (Journal of Critical Realism in Socio-Economics (JOCRISE), 2026)
A major paradigm is the civilizational understanding of reality that dictates everyday life; thus, a paradigm shift is of immense significance. This paper presents large-scale research into the factors contributing to such shifts, resulting in the "Planetary Oneness Paradigm." This framework embodies universal unity and interconnectedness, challenging today’s mainstream reductionist understanding, which is outdated, inaccurate, and static. The paper investigates the historical roots of our current crisis, beginning with the geocentric Ptolemaic paradigm. That view established an authoritarian "Divine Right" for rulers and granted humans planetary dominion as "God’s Children." The first paradigm shift, the Copernican Revolution, introduced a heliocentric universe, undermining authoritarianism while maintaining human status. The second shift, Darwinism, reframed humans as one species among many engaged in a struggle for survival. This, alongside the rise of Homo economicus, summarized life as "Survival of the Fittest," fueling aggression, colonialism, and environmental depredation. Concurrently, mainstream economics consolidated fundamental assumptions that the Industrial Revolution had already rendered false. This research identifies 59 such false assumptions and discovers that their opposites are true. These true opposites form the components of a third paradigm shift: a Shared World View. This view unifies Science and Religion, offering practical solutions to seemingly insoluble global problems—including universal basic income, wide capital ownership, and voluntary population stabilization. By changing material circumstances, this paradigm enables the evolution of a selfish Homo economicus into an environmentally responsible Homo co-operans, providing genuine hope for the future.